2016
DOI: 10.1017/s1368980016003116
|View full text |Cite
|
Sign up to set email alerts
|

Context-specific complementary feeding recommendations developed using Optifood could improve the diets of breast-fed infants and young children from diverse livelihood groups in northern Kenya

Abstract: Objective: To formulate age-and context-specific complementary feeding recommendations (CFR) for infants and young children (IYC) and to compare the potential of filling population-level nutrient gaps using common sets of CFR across age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(83 citation statements)
references
References 18 publications
4
79
0
Order By: Relevance
“…Thus, achieving nutritional goals for infants aged 6–8 months needed a substantial increase in nutrient-dense foods such as pulses and seeds, small dried fish, fruits and vegetables. Previous studies conducted in Kenya reported similar findings about the required dietary modification based on age group [ 15 , 18 ]. These two Kenyan studies revealed that achieving nutritional goals for infants and young children needs additional modification to local diets.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Thus, achieving nutritional goals for infants aged 6–8 months needed a substantial increase in nutrient-dense foods such as pulses and seeds, small dried fish, fruits and vegetables. Previous studies conducted in Kenya reported similar findings about the required dietary modification based on age group [ 15 , 18 ]. These two Kenyan studies revealed that achieving nutritional goals for infants and young children needs additional modification to local diets.…”
Section: Discussionsupporting
confidence: 69%
“…The linear programming (LP) approach can facilitate the optimal use of locally available foods to improve the dietary adequacy of vulnerable populations [ 14 ]. The LP approach needs to be carried out based on local availability and accessibility of nutrient-dense foods in the target population [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach was based on the recommended methods of Pro PAN and Optifood (Daelmans et al, ). Pro PAN and Optifood have been used to develop complementary feeding in several other countries where complementary feeding practices are inadequate (Ferguson et al, ; Hlaing et al, ; Santika et al, ; Skau et al, ; Vossenaar et al, ). Trials of improved practices (Manoff‐Group, ), a standard approach, were used to test the feasibility and acceptability of the FBCFRs.…”
Section: Discussionmentioning
confidence: 99%
“…Optifood is a linear programming software tool that can be applied to provide an evidence base for the development of messages used to improve IYCF practices (Daelmans et al, 2013). ProPAN and Optifood tools have previously been used to develop context-specific food-based complementary feeding recommendations in Kenya (Vossenaar et al, 2017); Myanmar (Hlaing et al, 2016); Cambodia (Skau et al, 2013); and Indonesia (Santika, Fahmida, & Ferguson, 2009).…”
Section: Introductionmentioning
confidence: 99%